Water use strategies of Ferula bungeana on mega-dunes in the Badain Jaran Desert - Qin, Jie; Si, Jianhua; Jia, Bing; Zhao, Chunyan; Zhou, Dongmeng; He, Xiaohui; Wang, Chunlin; Zhu, Xinglin (Frontiers in Plant Science, 2022)
In desert ecosystems, ephemeral plants have developed specialized water use strategies in response to long-term natural water stress. To examine the water use strategies of desert ephemeral plants under natural extreme drought conditions, we investigated the water absorption sources, water potential, hydraulic conductivity, and water use efficiency of Ferula bungeana at different elevations on the slopes of mega-dunes in the Badain Jaran Desert, Inner Mongolia, during a period of extreme drought. We found that the water utilized by F. bungeana was mostly absorbed from the 0–60 cm soil layers (80.47 ± 4.28%). With progression of the growing season, the source of water changed from the 0–30 cm soil layer to the 30-60 cm layer. The water potentials of the leaves, stems, and roots of F. bungeana were found to be characterized by clear diurnal and monthly variation, which were restricted by water availability and the hydraulic conductivity of different parts of the plant. The root hydraulic conductivity of F. bungeana was found to be considerably greater than that of the canopy, both of which showed significant diurnal and monthly variation. The water use efficiency of F. bungeana under extreme drought conditions was relatively high, particularly during the early and late stages of the growing season. Variations in water availability led to the regulation of water uptake and an adjustment of internal water conduction, which modified plant water use efficiency. These observations tend to indicate that the water use strategies of F. bungeana are mainly associated with the growth stage of plants, whereas the distribution pattern of plants on mega-dunes appeared to have comparatively little influence. Our findings on the water use of ephemeral plants highlight the adaptive mechanisms of these plants in desert habitats and provide a theoretical basis for selecting plants suitable for the restoration and reconstruction of desert ecosystems.